Accessibility and suitability of residential alcohol treatment for older adults: a mixed method study - Sarah Wadd; Maureen Dutton (BMC, 2018)
Abstract Background Whilst alcohol misuse is decreasing amongst younger adults in many countries, it is increasing in older adults. Residential rehabilitation (rehab) is a vital component of the alcohol treatment system, particularly for those with relatively complex needs and entrenched alcohol problems. In this study, we sought to find out to what extent rehabs in England have upper age limits that exclude older adults, whether rehabs are responsive to older adults' age-related needs and how older adults experience these services. Method This is a mixed method study. A search was carried out of Public Health England's online directory of rehabs to identify upper age thresholds. Semi-structured qualitative interviews were carried out with 16 individuals who had attended one of five residential rehabs in England and Wales since their 50th birthday. A researcher with experience of a later life alcohol problem conducted the interviews. Results Of the 118 services listed on Public Health England's online directory of rehabs, 75% stated that they had an upper age limit that would exclude older adults. Perceived differences in values, attitudes and behaviour between younger and older residents had an impact on older residents' experience of rehab. Activities organised by the rehabs were often based on physical activity that some older adults found it difficult to take part in and this could create a sense of isolation. Some older adults felt unsafe in rehab and were bullied, intimidated and subjected to ageist language and attitudes. Conclusion This study identified direct and indirect age discrimination in rehabs contrary to the law. Further research is required to find out if age discrimination exists in rehabs in other countries. Rehabs should remove arbitrary age limits and ensure that they are responsive to the needs of older adults.